The Big Mac Index, Consumer Price Index and Productivity Bias: Does Purchasing Power Parity Hypothesis Hold for Asian Countries? - Wong, Shiao Wern (2010)
The choice of an appropriate market basket to be used in conducting PPP tests has long been the object of debate in literature (Sarno and Taylor, 2002). Perhaps, the different compositions of goods and services and the existence of non-tradable elements in the market basket could play the important roles in explaining deviations from PPP. Given the issues on the choice of an appropriate price measure and the non-tradable productivity bias, therefore in this paper, we attempt to assess and compare the validity of long-run PPP using the single-good “basket” – the Big Mac index (BMI) and the conventional market basket of goods and services – the consumer price index (CPI), by taking the productivity bias into account, for a panel of 10 Asian countries, namely China, Hong Kong, Indonesia, Japan, Malaysia, Philippines, Russia, Singapore, Korea and Thailand, and 10 years with the sample period covers from 1999 to 2008. When Pedroni panel cointegration test is employed, the nominal exchange rates and the relative price ratio are found to be cointegrated in the long-run. However, no empirical evidence on PPP could be found when panel least square method is being adopted, regardless of whether the used of BMI or CPI as the price index, or with the productivity bias taken into account. With these, we therefore argue that the results produced tend to provide a little evidence in support of long-run PPP, particularly, the “weak” PPP as it is arguable that, although there may be a tendency for these series to move together in the long-run, their relationship however, does not necessarily be one-for-one, meaning that the changes in the nominal rate between the two countries does not necessarily equal to the changes in the relative price ratio.